(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Monetary compensation as an alternative remedy for unfair dismissal does not have an exact standard mechanism in the existing legal provision. Besides this, there are several gaps in the observation of the provisions of this remedy, which are often seen to oppose principles of conventional law. This is because of the inconsistent allocation of monetary awards, which differ for the facts of each case in terms of the calculation and percentage of deduction of monetary compensation. Awards are ’decisions made by a judge or arbitrator’. In fact, the principles of conventional law stress more on fairness between employer and employee in industrial relations. Therefore, this article employs the doctrinal research methodology to analyse wrongful dismissal cases based on the guidelines contained in the Second Schedule of the Industrial Relations Act 1967, as well as criteria applied to evaluate monetary compensation. The findings of this research are that there are inconsistencies in the evaluation of the amounts of monetary compensation awarded to employees involved. Therefore, there exists the need to create a more suitable and fair mechanism as required by the Industrial Relations Act 1967. Keywords: Monetary compensation, remedy, unfair dismissal, Second Schedule, award